2012
DOI: 10.5688/ajpe766104
|View full text |Cite
|
Sign up to set email alerts
|

A Graduate Student Mentoring Program to Develop Interest in Research

Abstract: Objective. To assess the impact of a graduate student mentoring program on student interest in research and postgraduate education and on graduate student confidence in mentoring. Methods. Undergraduate and pharmacy students (mentees) and graduate students (mentors) were matched and participated in the study, which required them to engage in at least 2 discussions regarding research and careers. Mentees completed a pre-and post-assessment of their perceptions of research, postgraduate training plans, and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Drug regulation was opted as preferred career choice by 21 (28.7%) students, clinical pharmacy by 18 (24.6%), hospital pharmacy by 11 (15), and teaching by 8 (10.5%). Factors involved in such selection were family influence (34.2%), anticipated income (24.6%), and personal interest (21.9%) [ Table 1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug regulation was opted as preferred career choice by 21 (28.7%) students, clinical pharmacy by 18 (24.6%), hospital pharmacy by 11 (15), and teaching by 8 (10.5%). Factors involved in such selection were family influence (34.2%), anticipated income (24.6%), and personal interest (21.9%) [ Table 1].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that uncertainty has been found among pharmacy students about research-related careers and postgraduate studies. [15,16] …”
Section: Discussionmentioning
confidence: 98%
“…Moreover, uncertainty has been found among pharmacy students about research-related careers. [17] CONCLUSION Fourth year students believed that pharmacy education and practice affect the health care system. Their favorite career areas were clinical pharmacy, industrial pharmacy, and hospital pharmacy.…”
Section: Discussionmentioning
confidence: 97%
“…Institutions affiliated with fellowship training programs should consider having their fellows serve as mentors to students. This approach would not only help improve students' perceptions of research and increase their interest but would also help prepare fellows for future mentor‐leader roles …”
Section: Strategies To Promote Research Fellowship Training Programsmentioning
confidence: 99%
“…This approach would not only help improve students' perceptions of research and increase their interest but would also help prepare fellows for future mentor-leader roles. 8 Fostering collaborations through the development of undergraduate research programs would provide students with opportunities for mentored learning by allowing them to work closely with faculty and fellows on a scholarly project. Students should be expected to formulate clinically relevant questions, propose hypotheses and solutions, examine the proposed solutions, and effectively communicate the outcome.…”
Section: Strategies To Promote Research Fellowship Training Programsmentioning
confidence: 99%